Small molecule inhibitors of mammalian glycosylation - Almahayni, Karim; Spiekermann, Malte; Fiore, Antonio; Yu, Guoqiang; Pedram, Kayvon; Möckl, Leonhard (Matrix Biology Plus, 2022)
Glycans are one of the fundamental biopolymers encountered in living systems. Compared to polynucleotide and polypeptide biosynthesis, polysaccharide biosynthesis is a uniquely combinatorial process to which interdependent enzymes with seemingly broad specificities contribute. The resulting intracellular cell surface, and secreted glycans play key roles in health and disease, from embryogenesis to cancer progression. The study and modulation of glycans in cell and organismal biology is aided by small molecule inhibitors of the enzymes involved in glycan biosynthesis. In this review, we survey the arsenal of currently available inhibitors, focusing on agents which have been independently validated in diverse systems. We highlight the utility of these inhibitors and drawbacks to their use, emphasizing the need for innovation for basic research as well as for therapeutic applications.
CRIS-Team Scopus Importer:2024-09-09
Keywords: Glycans; Glycocalyx; Glycosylation; Inhibitors; Small molecules